Sistem Pendukung Keputusan Penyesuaian Harga Dan Penambahan Stok Barang Sewa Berbasis Web Menggunakan Metode SAW Pada Studi Kasus Perusahaan Doctor COS - Khurniawan, Wahyu; Widhiyanta, Nurwahyudi (Journal of System Engineering and Technological Innovation, 2024)
Costume rental is currently a growing rental service business, but data management is generally done manually. At first, there were no problems with manual management, but as the number of costumes available and the costumes for rent increased, the amount of data that had to be managed increased, and manual data management became difficult, recorded transactions were also inefficient. it is necessary to build a computerized decision-making support system, such as adjusting the price of clothing and the quantity of goods on the market, as well as the accuracy and speed of presenting information. Building this system begins with collecting data about the system to be built, analyzing it, and designing a system based on these results using the Simple Additive Weighting (SAW) method. This method was chosen because the saw method is more popular because the calculation process is easier to understand, faster and simpler. The next step of the program can be made according to the design results. After the program is built, tests are run to check that the program built is as expected. The final step in this activity is to create system documentation which is realized in the form of a research report. The result of this research is a computer-assisted decision support application which, if implemented, is expected to overcome all data management problems in the rental business.